The effect of the severity of obstructive sleep apnea syndrome on telomere length - Tempaku, Priscila Farias [UNIFESP] (2016)
Aging is associated with an increase in the prevalence of obstructive sleep apnea syndrome (OSAS) as well as the shortening of telomeres. It is known that OSAS-related factors are stimuli that can contribute to the acceleration of cellular senescence. Thus, the present study aimed to compare the leukocyte telomere length (LTL) between OSAS patients and controls, as well as to verify the correlation between LTL and sleep parameters. We used DNA extracted of 928 individuals from EPISONO to measure the LTL by the quantitative real-time polymerase chain reaction. All individuals were subjected to one full-night polysomnography. LTL was significantly shorter in OSAS patients compared to controls. The results showed negative correlations between LTL and the following variables: apnea-hypopnea index, respiratory disturbance index, desaturation index and wake after sleep onset. LTL was positively correlated with sleep efficiency, total sleep time, basal, minimum and maximum oxygen saturation. Lastly, it was observed that OSAS severity was associated with shorter LTL even after adjusting for sex, age, years of schooling, body mass index, diabetes, stroke and heart attack. In conclusion, our study indicates the presence of an association between LTL and OSAS and a significant impact of severity of OSAS in telomeres shortening.